A classic ultrasound presentation of perinatal testicular torsion - Thomas Saliba; Giulia Negro (Paediatrica Indonesiana, 2026)
Perinatal testicular torsion, also known as neonatal testicular torsion, is defined by some authors as occurring either prenatally or within the first 30 days of life. It is estimated that 70% of these cases happen during pregnancy or shortly after birth.1-3 It is important to note that the radiological and clinical findings, as well as the mechanisms and surgical outcomes, associated with perinatal testicular torsion differ from those observed in older age groups [1]. Furthermore, a significant number of these cases occur bilaterally, highlighting the importance of timely diagnosis.1 The testicular salvage rate in 1988 was estimated to be around 5%, but more recent data presents a more optimistic outlook.1 Nevertheless, cases of prenatal torsion are generally considered unsalvageable.1 Perinatal testicular torsion is distinct because the torsion is extra-vaginal, in contrast to the intra-vaginal seen in older males, which is associated with a bell-clapper deformity.1-4 In cases of extra-vaginal torsion, the entire spermatic cord as along with the vas deferens, blood vessels, processus vaginalis, and surrounding fascias all undergo torsion, whereas in intra-vaginal torsion, only the testicle itself is affected.1,3,4